Nanostructured Pd/Sb2O3: A new and promising fuel cell electrocatalyst and non-enzymatic amperometric sensor for ethanol - Gonçalves, Rosana A. [UNESP]; Baldan, Maurício R.; Ciapina, Eduardo G. [UNESP]; Berengue, Olivia M. [UNESP] (Elsevier, 2019)
This manuscript describes the synthesis and structural/morphological characterization of Sb2O3 nanostructures modified by Pd nanoparticles and its use as a Fuel Cells electrocatalyst and as non-enzymatic amperometric sensor for ethanol. Interesting Sb2O3 surface modifications due to Pd nanoparticles were observed, such as the loss of spherical shape and the appearance of superficial pores. As an electrocatalyst Pd/Sb2O3 exhibited two times higher catalytic activity at a constant potential than carbon-supported Pd nanoparticles to oxidize ethanol in alkaline media (current densities of 348 μA cm−2 and 165 μA cm−2 at −0.3 V vs. Ag/AgCl 3.0 M, respectively). To the extent of our knowledge this result is the first one describing such an enhancement of the Pd activity only by means of alteration of the support. Moreover, as an amperometric sensor for ethanol, the electrode showed a linear response in a broad range of concentrations with a detection limit of 0.10 μM and sensitivity between of 1.47 to 1.00 μA mM−1 cm−2. The combined findings presented in this work revealed Pd/Sb2O3 can be a promising material for Direct Ethanol Fuel Cells and as a non-enzymatic amperometric sensor for ethanol.
Keywords: Amperometric sensor; Antimony oxide; Electrocatalysts; Ethanol; Fuel cells; Palladium